ROLE MODELLING, FEAR OF FAILURE, AND ENTREPRENEURIAL INTENTIONS: A STUDY OF FEMALE UNDERGRADUATES IN LAGOS STATE, NIGERIA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
This study investigates the influence of role modelling and fear of failure on the entrepreneurial intentions of female undergraduates in Lagos State, Nigeria, amidst rising economic challenges and increasing interest in entrepreneurship. The primary objectives are to examine how these factors impact entrepreneurial intentions and to identify the moderating roles of fear of failure, self-esteem and family support. A quantitative approach was employed, utilizing a questionnaire to collect data from a sample of 482 female students, selected through proportionate stratified random sampling technique from various educational institutions in Lagos State. Data analysis was conducted using Partial Least Square Structural Equation Modelling (PLS-SEM) to empirically analyse the relationships among the variables. The findings revealed a significant positive relationship between role modelling and entrepreneurial intention, while fear of failure and self-esteem do not have significant influence on entrepreneurial intention. Based on the findings, it is recommended that educational institutions in Lagos State focus on enhancing mentorship and role modelling initiatives to inspire female students towards entrepreneurship. Additionally, fostering strong social support systems, including family involvement, can help mitigate potential psychological barriers and further encourage entrepreneurial aspirations.